(untitled) (Academia Science Repository, 2023)
Markets are important components of modern economic systems, providing individuals and companies with the means of trading goods and services. Most markets involve a certain degree of risk, whether in the form of price fluctuations, supply uncertainty, or other market uncertainties. In this article we will explore the concept of market risk and its implications for businesses and investors.